A novel 1.6 kV high voltage low current step-up DC-DC converter with cockcroft-walton voltage multiplier for power supply modules - Murad, S.A.Z. (Penerbit UTM Press, 2019)
A high dc voltage is commonly used in many process industries in testing, research laboratories and others. Currently, a high voltage dc is implemented using transformer. In this paper, a novel high voltage low current transformerless step-up dc-dc converter is presented. The proposed design consists of two step-up dc-dc converters with negative feedback signal and 15 stages of Cockcroft-Walton (CW) voltage multiplier. The dc input voltage of 5 V triggers the first step-up dc-dc converter circuit to generate 30 V dc voltage and the second step-up dc-dc converter circuit boosts up to 100 V dc voltage. Further, diode-capacitor multiplier circuit is connected at the final stage to achieve 1.6 kV dc output voltages at 200 kHz switching frequency. The simulation results indicate that the proposed dc-dc converter can generate 1.548 kV dc voltage with a load current of 0.16 mA at 10 MÎ© load resistor. Meanwhile, the experiment results show that the proposed dc-dc converter can generate 1.475 kV dc voltage with 80 efficiency. The results validate both the simulation and experimental of the proposed high dc voltage power supply module. Â© 2019 Penerbit UTM Press.